Fine mapping and conditional analysis identify a new mutation in the autoimmunity susceptibility gene BLK that leads to reduced half-life of the BLK protein. Issue 7 (13th June 2012) - Delgado-Vega, Angélica M; Dozmorov, Mikhail G; Quirós, Manuel Bernal; Wu, Ying-Yu; Martínez-García, Belén; Kozyrev, Sergey V; Frostegård, Johan; Truedsson, Lennart; de Ramón, Enrique; González-Escribano, María F; Ortego-Centeno, Norberto; Pons-Estel, Bernardo A; et al.
Abstract : Objectives: To perform fine mapping of the autoimmunity susceptibility gene BLK and identify functional variants involved in systemic lupus erythematosus (SLE). Methods: Genotyping of 1163 European SLE patients and 1482 controls and imputation were performed covering the BLK gene with 158 single-nucleotide polymorphisms. Logistic regression analysis was done using PLINK and conditional analyses using GENABEL's test score. Transfections of BLK constructs on HEK293 cells containing the novel mutation or the wild type form were analysed for their effect on protein half-life using a protein stability assay, cycloheximide and western blot. CHiP-qPCR for detection of nuclear factor κ B (NFkB) binding. Results: Fine mapping of BLK identified two independent genetic effects with functional consequences: one represented by two tightly linked associated haplotype blocks significantly enriched for NFκB-binding sites and numerous putative regulatory variants whose risk alleles correlated with low BLK mRNA levels. Binding of NFkBp50 and p65 to an associated 1.2 Kb haplotype segment was confirmed. A second independent genetic effect was represented by an Ala71Thr, low-frequency missense substitution with an OR=2.31 (95% CI 1.38 to 3.86). The 71Thr decreased BLK protein half-life. Conclusions: These results show that rare and common regulatory variants in BLK are involved in disease susceptibility and both, albeit independently, lead to reduced levels of BLK protein.